Metabolism of sucrose in a non-fermentative Escherichia coli under oxygen limitation - Olavarria, Karel; Fina, Albert; Velasco, Mariana I.; Van Loosdrecht, Mark C. M.; Wahl, Sebastian Aljoscha (Applied Microbiology and Biotechnology, 2019)
Biotechnological industry strives to develop anaerobic bioprocesses fueled by abundant and cheap carbon sources, like sucrose. However, oxygen-limiting conditions often lead to by-product formation and reduced ATP yields. While by-product formation is typically decreased by gene deletion, the breakdown of oligosaccharides with inorganic phosphate instead of water could increment the ATP yield. To observe the effect of oxygen limitation during sucrose consumption, a non-fermentative Escherichia coli K-12 strain was transformed with genes enabling sucrose assimilation. It was observed that the combined deletion of the genes adhE, adhP, mhpF, ldhA, and pta abolished the anaerobic growth using sucrose. Therefore, the biomass-specific conversion rates were obtained using oxygen-limited continuous cultures. Strains performing the breakdown of the sucrose by hydrolysis (SUC-HYD) or phosphorolysis (SUC-PHOSP) were studied in such conditions. An experimentally validated in silico model, modified to account for plasmid and protein burdens, was employed to calculate carbon and electron consistent conversion rates. In both strains, the biomass yields were lower than expected and, strikingly, SUC-PHOSP showed a yield lower than SUC-HYD. Flux balance analyses indicated a significant increase in the non-growth-associated ATP expenses by comparison with the growth on glucose. The observed fructose-1,6-biphosphatase and phosphoglucomutase activities, as well as the concentrations of glycogen, suggest the operation of ATP futile cycles triggered by a combination of the oxygen limitation and the metabolites released during the sucrose breakdown.
CRIS-Team Scopus Importer:2022-01-11
Keywords: Carbon storage regulator A; Data reconciliation; Flux balance analysis; Plasmid burden; Sucrose phosphorolysis